Methyltransferase-Like 3 Rescues the Amyloid-beta protein-Induced Reduction of Activity-Regulated Cytoskeleton Associated Protein Expression via YTHDF1-Dependent N6-Methyladenosine Modification - Xu, Chenhaoyi; Huang, Huanghuang; Zhang, Min; Zhang, Pei; Li, Zezhi; Liu, Xueyuan; Fang, Min (Frontiers in Aging Neuroscience, 2022)
Activity-regulated cytoskeleton-associated protein (ARC) is activated by the induction of long-term potentiation and plays an important role in the synaptic plasticity of memory consolidation. Previous studies have shown that abnormal expression of ARC in the brains of patients with Alzheimer’s disease (AD) leads to the disturbance of synaptic plasticity. ARC expression is mainly regulated by transcriptional and post-translational modification. However, it is unclear whether N6-methyladenosine (m6A) engages in the epigenetic modification of ARC. The AlzData database was used to analyze the brain of AD patients, and Aβ-induced cell models were used. We revealed that ARC expression was reduced in AD patients and Aβ-induced cell models. There were five m6A modification sites of ARC mRNA that were predicted by the SRAMP database, and ARC mRNA was confirmed as the target gene of methyltransferase-like 3 (METTL3) by MeRIP. Amyloid-beta protein (Aβ) repressed the m6A modification. Knockdown of METTL3 decreased ARC mRNA m6A modification and reduced ARC protein expression, while overexpression of METTL3 rescued ARC expression after Aβ treatment. Knockdown of YTH domain family, member 1 (YTHDF1) decreased ARC protein expression, while the overexpression of YTHDF1 could not rescue the loss of ARC protein expression after 3-deazaadenosine treatment or knockdown of METTL3. Our findings identify that METTL3 rescues the Aβ-induced reduction of ARC expression via YTHDF1-Dependent m6A modification, which suggests an important mechanism of epigenetic alteration in AD.